Rhigonema naylae n. sp. (Rhigonematomorpha: Rhigonematidae) a new parasitic nematode from a Japanese polydesmid millipede (Polydesmida: Xystodesmidae) - Morffe, Jans; Hasegawa, Koichi (Zootaxa, 2017)
Rhigonema naylae n. sp. (Rhigonematomorpha: Rhigonematidae) is described from the hindgut of the polydesmid millipede Parafontaria laminata (Attems, 1909) (Polydesmida: Xystodesmidae), from Aichi prefecture, Japan. The new species is characterized by having a medium sized body in both sexes, the cephalic collar partially fused to the body cuticle, but not overhanging the body contour; cervical region densely covered in short, fine microtrichs that extend from the posterior margin of the cephalic collar to ca. 1.5 oesophagus lengths posterior to the basal bulb; tail short and conoid, subulate in females and with a short mucron in males; female genital tract of Type 2 according to Adamson (1987); males with a complement of 23 copulatory papillae, one post-cloacal pair lateral and two sub-dorsal. This arrangement of copulatory papillae is typical from the African/Asian species and contributes to the segregation of R. naylae n. sp. from the American/Australasian taxa. Description is supplemented by SEM images. Partial sequences of the D2-D3 LSU rDNA and 18S SSU rDNA were obtained. This constitutes the second species of the genus Rhigonema Cobb, 1898 described from the Japanese archipelago.